Diabetes Disease Analysis Using Rough Soft Set - Manimaran, M.; Praba, B.; Deepa, G.; M. Chandrasekaran, V.; Venkatesan, Krishnamoorthy (International Journal of Engineering and Technology, 2018)
Diabetes is a noteworthy medical issue in both modern and creating nations, and its frequency is rising apparently. It is a metabolic disease in which the person who has been affected will have high blood glucose or high blood sugar. It is mainly because of inadequate production of insulin or the body’s cells do not respond to insulin. In some special cases it may be due to both the reasons. This disease causes a lot of health issues in humans’ life. Rough set and soft set theory plays a major role for dealing with uncertainty and it has been applied in many fields. In this paper we aim at finding the age group of people in which maximum diabetes mellitus occurs using the concept of rough soft set and rough soft decision set.